Construction and Characterization of a Bacterial Artificial Chromosome Library for the Hexaploid Wheat Line 92R137. (5th May 2014) - Zeng, Qingdong; Yuan, Fengping; Xu, Xin; Shi, Xue; Nie, Xiaojun; Zhuang, Hua; Chen, Xianming; Wang, Zhonghua; Wang, Xiaojie; Huang, Lili; Han, Dejun; Kang, Zhensheng
Abstract : For map-based cloning of genes conferring important traits in the hexaploid wheat line 92R137, a bacterial artificial chromosome (BAC) library, including two sublibraries, was constructed using the genomic DNA of 92R137 digested with restriction enzymes Hind III and Bam HI. The BAC library was composed of total 765, 696 clones, of which 390, 144 were from the Hind III digestion and 375, 552 from the Bam HI digestion. Through pulsed-field gel electrophoresis (PFGE) analysis of 453 clones randomly selected from the Hind III sublibrary and 573 clones from the Bam HI sublibrary, the average insert sizes were estimated as 129 and 113 kb, respectively. Thus, the Hind III sublibrary was estimated to have a 3.01-fold coverage and the Bam HI sublibrary a 2.53-fold coverage based on the estimated hexaploid wheat genome size of 16, 700 Mb. The 765, 696 clones were arrayed in 1, 994 384-well plates. All clones were also arranged into plate pools and further arranged into 5-dimensional (5D) pools. The probability of identifying a clone corresponding to any wheat DNA sequence (such as gene Yr26 for stripe rust resistance) from the library was estimated to be more than 99.6%. Through polymerase chain reaction screening the 5D pools with Xwe173, a marker tightly linked to Yr26, six BAC clones were successfully obtained. These results demonstrate that the BAC library is a valuable genomic resource for positional cloning of Yr26 and other genes of interest.